Perfect square......with additions?

Algebra Level 2

Find the least positive integer n n such that 2 8 + 2 11 + 2 n 2^8+2^{11}+2^n is a perfect square.


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Jovan Boh Jo En
May 5, 2018

Let x 2 = 2 8 + 2 11 + 2 n x^2=2^8+2^{11}+2^n , where x x is an integer. Thus, x = 2 8 + 2 11 + 2 n x=\sqrt{2^8+2^{11}+2^n} = 2 8 ( 1 + 2 3 + 2 n 8 ) =\sqrt{2^8\left(1+2^3+2^{n-8}\right)} = 2 8 1 + 2 3 + 2 n 8 =\sqrt{2^8}\cdot\sqrt{1+2^3+2^{n-8}} Since 2 8 \sqrt{2^8} is an integer, 1 + 2 3 + 2 n 8 \sqrt{1+2^3+2^{n-8}} will be also an integer as well. 1 + 2 3 + 2 n 8 1+2^3+2^{n-8} = 9 + 2 n 8 =9+2^{n-8} Then, try a few perfect squares bigger than 9 and substitute in this equation to find x x . If it equals to 16: \color{#3D99F6}\text{If it equals to 16:} 9 + 2 n 8 = 16 9+2^{n-8}=16 2 n 8 = 7 2^{n-8}=7 7 is not a power of 2. Thus, this cannot be equal to 16. \color{#3D99F6}\text{7 is not a power of 2. Thus, this cannot be equal to 16.} If it equals to 25: \color{#20A900}\text{If it equals to 25:} 9 + 2 n 8 = 25 9+2^{n-8}=25 2 n 8 = 16 2^{n-8}=16 2 n 8 = 2 4 2^{n-8}=2^4 n 8 = 4 n-8=4 n=12 \color{#20A900}\text{n=12}

X X
May 5, 2018

2 8 + 2 11 = 4 8 2 2^8+2^{11}=48^2 ,let the perfect square = a 2 =a^2 ,then a 2 4 8 2 = ( a + 48 ) ( a 48 ) = 2 n a^2-48^2=(a+48)(a-48)=2^n .
Let a + 48 = 2 b a+48=2^b and a 48 = 2 c a-48=2^c , 2 b 2 c = 96 , 2 b 5 2 c 5 = 3 2^b-2^c=96,2^{b-5}-2^{c-5}=3 .
The only solution is 2 2 2 0 = 3 , b = 7 , c = 5 , b + c = n = 12 2^2-2^0=3,b=7,c=5,b+c=n=\boxed{12}

Edwin Gray
Sep 19, 2018

Note that 2^8 + 2^11 = 256 + 2048 = 2304 = 48^2. So the problem becomes to find the smallest n such that 48^2 + 2^n = x^2, or 2^n = (x - 48)(x + 48). Let x - 48 = 2^t, and x + 48 = 2^(n - t). Therefore 96 = (2^t) (2^(n - 2t) - 1) = 32*3, So t = 5, and 2^(n - 10) - 1 = 3, or 2^(n - 10) = 4 = 2^2, so n - 10 = 2, or n = 12. Ed Gray

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...